A project designed to examine, for the first time, the health records of adult prisoners in Northern Ireland and their linkage to other available health data: the test case of prisoner post-release mortality risk. - Janine Cooper; Dermot O'Reilly; Richard Kirk; Trish Kelly; Rachel Gibbs; Michael Donnelly (International Journal of Population Data Science, 2022)
A project designed to examine, for the first time, the health records of adult prisoners in Northern Ireland and their linkage to other available health data: the test case of prisoner post-release mortality risk